How do you simplify #((9x^6 y^-3 z)/(18xy^3 z^-5))#?

1 Answer
Apr 11, 2016

Answer:

#=(x^(5 ) z ^ 6) / ( 2y^(6)#

Explanation:

#(9x^6y^-3z) / ( 18 x y ^3 z ^-5#

#=(9 * x^6 * y^-3 * z) / ( 18 * x * y ^3 * z ^-5#

#=(cancel9 / cancel18 ) * ( x^6 * y^-3 * z) / ( x * y ^3 * z ^-5#

#=(1/2 ) * ( x^6 * y^-3 * z) / ( x * y ^3 * z ^-5#

  • Applying property:
    #color(blue)(a^m / a ^n = a ^(m-n)#

#=(1/2 ) * ( x^(6 - 1)) * ( y^(-3 - 3 )) * ( z ^ ( 1 - ( -5))) #

#=(1/2 ) * x^(5 ) * y^(-6) * z ^ ( (1 + 5)) #

#=(1/2 ) x^(5 ) y^(-6) z ^ 6#

#=(x^(5 ) z ^ 6) / ( 2y^(6)#